Determining The Settling Velocity Based On Size And Shape Of Gold Particle To Improve The Design Of Sluice Box - Basirun, Rusella Ira Runella (Universiti Sains Malaysia, 2017)
The use of mercury in Artisanal Small Scale Mining (ASGM) has led to the global problem. In this study, the problem faced in sluice box had been investigated and the data involved was obtained from the literature study. The calculation was justified from the literature study based on Stokes’ and Newton’s law. Next, the result obtained that influencing the settling velocity gave information about the behaviour of the particles sizes and shape. Based on the result, the problem of too fine particle size and irregular or flakiness shape can affect the particle to settle. In addition, the effect of degree of inclination of sluice box, and different value of flow rate also being carried out by calculation justification. However, this design is not enough to prove whether it is successful or not just by using calculation method. The proposed design need to be tested by further experimental and simulation method.